2012
DOI: 10.1021/es303468y
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric PCDD/F Concentrations in 38 Cities of China Monitored with Pine Needles, a Passive Biosampler

Abstract: Many studies have shown that pine needles are a good biomonitor for atmospheric concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs). However, this biomonitor has not been tested in large areas, and the quantitative relationship between concentrations in pine needles and air has not been established. In the present study, we collected pine needles from 38 cities in China. The concentrations of 2,3,7,8-PCDD/ Fs were measured by gas chromatography combined with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…The PCDD/Fs concentrations increased in the order Hangzhou Botanical Garden < Yuquan Campus of Zhejiang University < MWIP, which is reasonable because the anthropogenic activities and PCDD/Fs emissions also decreased in this order. This result supports the conclusion made by Chen et al (2012) that pine needles are good biosamplers. They studied the PCDD/Fs concentrations in the pine needles from 38 cities in China and found that the PCDD/Fs varied over three orders of magnitude and related well to the air pollution in the cities (Chen et al 2012).…”
Section: Pcdd/fs Concentrations In Pine Needles With Varying Age and supporting
confidence: 92%
See 4 more Smart Citations
“…The PCDD/Fs concentrations increased in the order Hangzhou Botanical Garden < Yuquan Campus of Zhejiang University < MWIP, which is reasonable because the anthropogenic activities and PCDD/Fs emissions also decreased in this order. This result supports the conclusion made by Chen et al (2012) that pine needles are good biosamplers. They studied the PCDD/Fs concentrations in the pine needles from 38 cities in China and found that the PCDD/Fs varied over three orders of magnitude and related well to the air pollution in the cities (Chen et al 2012).…”
Section: Pcdd/fs Concentrations In Pine Needles With Varying Age and supporting
confidence: 92%
“…This result supports the conclusion made by Chen et al (2012) that pine needles are good biosamplers. They studied the PCDD/Fs concentrations in the pine needles from 38 cities in China and found that the PCDD/Fs varied over three orders of magnitude and related well to the air pollution in the cities (Chen et al 2012).…”
Section: Pcdd/fs Concentrations In Pine Needles With Varying Age and supporting
confidence: 92%
See 3 more Smart Citations